Detection of α-thalassemia-1 Southeast Asian and Thai type deletions and β-thalassemia 3.5-kb deletion by single-tube multiplex real-time PCR with SYBR green 1 and high-resolution melting analysis - Pornprasert S. (2017)
Background: Prevention and control of thalassemia requires simple, rapid, and accurate screening tests for carrier couples who are at risk of conceiving fetuses with severe thalassemia. Methods: Single-tube multiplex real-time PCR with SYBR Green1 and high-resolution melting (HRM) analysis were used for the identification of α-thalassemia-1 Southeast Asian (SEA) and Thai type deletions and β-thalassemia 3.5-kb gene deletion.The results were compared with those obtained using conventional gap-PCR. DNA samples were derived from 28 normal individuals, 11 individuals with α-thalassemia-1 SEA type deletion, 2 with α-thalassemia-1 Thai type deletion, and 2 with heterozygous β-thalassemia 3.5-kb gene deletion. Results: HRM analysis indicated that the amplified fragments from α-thalassemia-1 SEA type deletion, α-thalassemia-1 Thai type deletion, β-thalassemia 3.5-kb gene deletion, and the wild-type β-globin gene had specific peak heights at mean melting temperature (T m ) values of 86.89°C, 85.66°C, 77.24°C, and 74.92°C, respectively. The results obtained using single-tube multiplex real-time PCR with SYBR Green1 and HRM analysis showed 100% consistency with those obtained using conventional gap-PCR. Conclusions: Single-tube multiplex real-time PCR with SYBR Green1 and HRM analysis is a potential alternative for routine clinical screening of the common types of α- and β-thalassemia large gene deletions, since it is simple, cost-effective, and highly accurate. © The Korean Society for Laboratory Medicine.